Marc Nagtzaam : Vlak. (Amsterdam : Roma Publications Amsterdam, 2005)
Eight drawings by Marc Nagtzaam: (As Far as I'm Concerned), (13 JAN.1973 / JULY 4, 1973), (Ins and Outs), (Not One, Not Two but Three), (The Sound of Something Happening), (Pantone), (Polaroid), (To the White Sea and Beyond).
Engels
boek
Keywords: Nagtzaam, Marc